Mice produced by mitotic reprogramming of sperm injected into haploid parthenogenotes - Toru Suzuki (Nature Portfolio, 2016)
It is unclear what regulates gamete reprogramming competence. Here, the authors inject sperm into parthenogenetic embryos, generating viable offspring and show that mouse embryos in the mitotic cell cycle can reprogram sperm for full term development.